PENDIDIKAN, PENGALAMAN DAN INDEPENDENSI PENGARUHNYA TERHADAP PROFESIONALISME AUDITOR (Studi Empiris Pada Kantor Akuntan Publik di Surabaya ) - Trisnaningsih, Sri; Dwi Haryadi, dan Deddy (Journal of Accounting and Strategic Finance, 2009)
The research aims to prove the empirical influence of education, experience, independence and professionalism of the auditors and the auditors to prove the most dominant factors that affect the professionalism of auditors. The sample used was 31 with KAP KAP each represented one of the respondents in the KAP in Surabaya. This sampling technique using Simple Random Sampling. The research used four variable such as: education, experience ,independence as independent variables and the professionalism of auditors as a dependent variable. Analyzed using multiple regression linier analysis. The results is the independence of auditors a significant effect on the professionalism of auditors, while the education and experience does not affect significantly to the professionalism of auditors, so this hypothetical research: (a) to the hypothetical-1 which states that education, experience, independence and professionalism of auditors affect KAP in Surabaya, the truth incorrect (b) to the hypothetical-2 that states that experience more dominant effect on the professionalism of auditors KAP incorrect. Keywords: Education, Experience, Independence and Profesionalism of Auditor.